2012
DOI: 10.2166/wst.2012.043
|View full text |Cite
|
Sign up to set email alerts
|

Use of submerged anaerobic membrane bioreactor (SAMBR) containing powdered activated carbon (PAC) for the treatment of textile effluents

Abstract: This work investigated the use of submerged anaerobic membrane bioreactors (SAMBRs) in the presence and absence of powdered activated carbon (PAC) for the treatment of genuine textile wastewater. The reactors were operated at 35 °C with an HRT of 24 h and the textile effluent was diluted (1:10) with nutrient solution containing yeast extract as the source of the redox mediation riboflavin. The results showed that although both SAMBRs exhibited an excellent performance, the presence of PAC inside SAMBR-1 enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 0 publications
4
24
1
1
Order By: Relevance
“…During phases 4 (with yeast extract) and 5 (without yeast extract) the reactors were fed raw textile wastewater (without dilution) and the presence of yeast extract led to color removal efficiencies 3 times higher in SAMBR-1 and 2.7 higher in SAMBR-2. These results are in accordance with the literature (Baêta et al, 2012;Baêta et al, 2013), confirming that the kinetics of azo dye (one on the many dye classes found in textile wastewater) degradation is accelerated in the presence of redox mediators such as riboflavin, which have intermediate reduction potential values. It is important to highlight that there is only a handful of studies evaluating the effect of redox mediators on color removal of real textile wastewater.…”
Section: Color Efficiency Removal (%)supporting
confidence: 92%
“…During phases 4 (with yeast extract) and 5 (without yeast extract) the reactors were fed raw textile wastewater (without dilution) and the presence of yeast extract led to color removal efficiencies 3 times higher in SAMBR-1 and 2.7 higher in SAMBR-2. These results are in accordance with the literature (Baêta et al, 2012;Baêta et al, 2013), confirming that the kinetics of azo dye (one on the many dye classes found in textile wastewater) degradation is accelerated in the presence of redox mediators such as riboflavin, which have intermediate reduction potential values. It is important to highlight that there is only a handful of studies evaluating the effect of redox mediators on color removal of real textile wastewater.…”
Section: Color Efficiency Removal (%)supporting
confidence: 92%
“…Such results evidence the contribution of PAC in the removal of organic matter in anaerobic systems, as previously demonstrated[12].…”
supporting
confidence: 89%
“…It can be seen that throughout operational phases 2 and 3 the efficiency of RGYRNL removal was significantly higher (p-value < 0.05) in the reactor An2 (80.6% phase 2 and 90.4% phase 3) when compared to reactor An1 (78.2% phase 2 and 86.1% phase 3). Such outcome was expected, since other studies performed by our research group also showed higher color removal in anaerobic reactors operated with PAC (4 g/L) when they were fed with synthetic and industrial effluents [12,24]. …”
Section: Evaluation Of Aerobic Post-treatment In the Removal Of Residsupporting
confidence: 69%
See 2 more Smart Citations